Pengembangan Bakteri Anaerob Lokal Untuk Mengolah Air Limbah Organik - Dhanus Suryawan; Rahyani Ermawati (Balai Besar Kimia dan Kemasan, 1996)
The research on lokal anaerobic bacteria for degradation of organic waste water was carried out by drawandfill methods, at room temperature of 30 ± 2 °C. At initial stage, synthetic waste water was used. At a TOC loading rate of 0,5 gll/d had no major effects on the seed from cattle breeding waste disposal lagoon, river bottom and acclimated granullar bacteria, TOC removal efficiency was high about 95 %. However, TOC removal efficiency of the seed from paper industrial waste disposal lagoon was not stable, decreased during the time of treatment, it indicated that the degradation process was only on acidification step.